PRICE ELASTICITY IN GENERATION Z LIFESTYLE COFFEE CONSUMPTION : AN ANALYTICAL LITERATURE REVIEW - Tamariska Fendy Putri; Lis Sintha (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study analyzes price elasticity in emotional product consumption, focusing on lifestyle coffee among Generation Z consumers. The study applies an analytical literature review with thematic analysis to synthesize research on coffee demand, price elasticity, hedonic consumption, lifestyle-based purchasing, social media influence, fear of missing out (FoMO), and perceived value. A replicable search protocol was developed using Google Scholar, ScienceDirect, SAGE Journals, Emerald Insight, SpringerLink, Taylor & Francis Online, and Garuda/SINTA-indexed Indonesian journals. The search prioritized publications from 2016 to 2026, while seminal works on hedonic consumption and thematic analysis were retained when conceptually necessary. After relevance-based screening, 25 sources were synthesized into four themes. The review finds that lifestyle coffee demand among Generation Z is not shaped by price and functional utility alone, but also by hedonic value, lifestyle identity, brand experience, social media visibility, and FoMO-driven trend participation. These factors may reduce price sensitivity and support higher price tolerance, especially when consumers perceive coffee as a symbolic and experiential product. However, this inelasticity is conditional; consumers may become price sensitive when quality, ambience, digital relevance, or emotional value declines. The study concludes that lifestyle coffee businesses should apply value-based and experience-driven pricing rather than relying solely on cost-based or competition-based pricing.